Green Gentrification and Environmental Injustice: A Discussion Based on the New Pinheiros River Program, São Paulo, Brazil - Alves, Estela Macedo; Paz, Mariana Gutierres Arteiro da; Fracalanza, Ana Paula (Frontiers in Sustainable Cities, 2021)
Through the analysis of the New Pinheiros River Program, São Paulo, Brazil, the differences in the solutions presented are considered to implement environmental projects in different territories over the same sub-basin. Vulnerable neighborhoods upstream will receive only basic infrastructure; while Marginal Pinheiros, a rich place, will be contemplated with aditional leisure, sports and cultural equipments. The general aim is to analyze the process of capitalist production of the Pinheiros River depolluting program area, proposed by the São Paulo State government in 2019, as well as green gentrification and creation of environmental injustice. Methodology consists of bibliographic research and analysis of the program's documents and speeches of people in charge. Global South cities have been experimenting environmental injustice as a result of financial capital investments.